Factors affecting ranging behaviour in commercial free-range hens. Issue 1 (March 2016) - PETTERSSON, I.C.; FREIRE, R.; NICOL, C.J.
Abstract : Many studies have assessed use of the outdoor 'range' area on free-range laying farms, and have revealed that percentage range use at any one time rarely exceeds 50% of the flock, and is sometimes below 10%. What constitutes a 'good' range use is difficult to determine without better knowledge of ranging bout lengths under ideal conditions. Well documented factors that affect percentage range use include prevailing weather, flock size and shelter on the range. Other factors such as pophole design, internal and external stocking density and system design appear to play a role although their effects are not as clear and more research would be valuable to truly understand their relevance. Factors affecting bird distribution on the range are also reviewed.